Effect of a neural relay on liver regeneration in mice: activation of serotonin release from the gastrointestinal tract. Issue 3 (31st January 2018) - Inoue, Ryosuke; Kamimura, Kenya; Nagoya, Takuro; Sakai, Norihiro; Yokoo, Takeshi; Goto, Ryo; Ogawa, Kohei; Shinagawa‐Kobayashi, Yoko; Watanabe‐Mori, Yukari; Sakamaki, Akira; Abe, Satoshi; Kamimura, Hiroteru; et al.
Abstract : The development of therapeutic options to promote hepatic regeneration following severe liver injury is essential. While humoral factors have been reported as mechanisms of liver regeneration, the contributions of interorgan communication to liver regeneration have not been reported. In this study, we examined the effect of a neural relay on liver regeneration via activation of serotonin release from the gastrointestinal (GI) tract. Our results demonstrated that the afferent visceral nerve from the liver activates the efferent vagus nerve from the brain, leading to activation of serotonin release from the GI tract and contributing to liver regeneration. While it is difficult to apply these results directly to human health, we believe that this study may represent a step toward developing essential therapeutics to promote liver regeneration. Abstract : This study demonstrated that a neural relay, activated by liver damage, contributed to hepatic regeneration. The afferent visceral nerve from the damaged liver stimulated the efferent vagus nerve from the brain, leading to activation of serotonin release from the gastrointestinal tract, which contributed to liver regeneration. These results may represent a step toward developing essential therapeutics to promote liver regeneration.